(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Myocardial infarction (MI) is the leading cause of morbidity and mortality in the worldwide. A high level of oxidative stress is linked to myocardial infraction, which results in induced damage by free radicals, lipid peroxidation, and deficient energy production. Coenzyme Q10 is essential for the ATP production process. It is therefore necessary for all energy-dependent mechanisms in cardiac cells, which are highly sensitive to CoQ10 insufficiency caused by cardiovascular events. With CoQ10 enhancing cellular bioenergetics as well as its antioxidant activity, it may play a role in the prevention and treatment of heart diseases. In this study, we measured serum levels of enzymatic markers of tissue damage including High-Sensitivity Cardiac Troponin (hs-cTnT) and Creatine Kinase MB (CPK-MB) and the markers of oxidative stress including Coenzyme Q10 (CoQ10) and Malondialdehyde (MDA).in addition to lipid profile in 50 patients with MI and 45 control subjects. We also studied correlations between CoQ10 with the above biomarkers. This study found that serum CoQ10 levels (nmol/L) were lower in MI patients than in control group (10.38 vs 77.33). The levels of MDA (ng/mL) were significantly higher in MI patients than in control group (1847 vs 398.3). There was a significant increase in serum levels of hs-cTnT (pg/mL) and CPK-MB(IU/L) in MI patients than in control group (1406 vs 3.143) (107.9 vs 11.46). Serum MDA levels significantly increased in patients with MI in comparison to healthy subjects and the coenzyme Q10 levels were significantly decreased in patients with MI than in controls.